2006
DOI: 10.1523/jneurosci.1727-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Odorant Deprivation Reversibly Modulates Transsynaptic Changes in the NR2B-Mediated CREB Pathway in Mouse Piriform Cortex

Abstract: The olfactory system is an outstanding model for understanding activity-dependent neuronal plasticity in mammals. Olfactory sensory neurons (OSNs) in the periphery project onto mitral/tufted cells in the olfactory bulb (OB) and these mitral/tufted cells in turn project to piriform cortex (PC). Numerous studies have examined changes in OB after a permanent OSN ablation, but little is known about "trans-transsynaptic" changes taking place in the PC. Permanent zinc sulfate lesion of the olfactory epithelium resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 125 publications
3
26
0
Order By: Relevance
“…A previous study showed that unilateral naris obstruction for Ͼ30 d enhances the intracortical association fiber input to the olfactory cortex of the adult rat (Best and Wilson, 2003). Unilateral naris obstruction for 5 d causes downregulation of the NMDA receptor NR2B subunit and phospho-CREB, specifically in layer IIb pyramidal cells of the mouse OC (Kim et al, 2006). These results raise the possibility that similar changes may occur in the AON during rapid compensatory switching of binasal inputs.…”
Section: Discussionmentioning
confidence: 69%
“…A previous study showed that unilateral naris obstruction for Ͼ30 d enhances the intracortical association fiber input to the olfactory cortex of the adult rat (Best and Wilson, 2003). Unilateral naris obstruction for 5 d causes downregulation of the NMDA receptor NR2B subunit and phospho-CREB, specifically in layer IIb pyramidal cells of the mouse OC (Kim et al, 2006). These results raise the possibility that similar changes may occur in the AON during rapid compensatory switching of binasal inputs.…”
Section: Discussionmentioning
confidence: 69%
“…CREB phosphorylation in the piriform cortex has been shown to be responsive to several stimuli (Alvarez-López et al, 2004; Dere et al, 2008; Estrada and Isokawa, 2009; Kim et al, 2006; Pandey et al, 2001a, b; Wang et al, 2007). However, this is the first study, to our knowledge, to examine CREB activation in the piriform cortex after inhibitory avoidance training, revealing no evidence for pCREB increases after training in either young or aged rats.…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic control of BACE and AβPP products is especially well shown by unilateral closure of the external nares. Unilateral closure, blocking stimuli from reaching olfactory receptors in the olfactory epithelium, suppresses synaptic and metabolic activity both in the olfactory bulb (OB) and in downstream cortical sites [27,31]. The mitochondrial enzymes cytochrome oxidase and succinic dehydrogenase (indicators of brain metabolic activity) decline.…”
Section: Metabolic Activity Regulates Bace Activitymentioning
confidence: 99%